The Future Perspectives of Agricultural Graduates and Sustainable Agriculture in Sudan - Haroun Mohamed Adam, Abubaker (Journal of Agronomy Research, 2019)
The objectives of this study were to assess the Quality of Agricultural Graduates, employers’ perceptions of the employability and skills. A descriptive, analytical statistics, multistage random sampling method was adopted. Where two types of questionnaires were distributed to the Graduates and institutions associated with Sustainable agriculture (SA). The collected data was analyzed by Statistical Packages for Social Sciences (SPSS). The results revealed some respondents began higher education in Arabic (66.7%), while others in English (33.3%). The respondents faced with difficulties in understanding the courses due to teaching methods (36.7%), language (33.3%), and curriculum (30%). The result indicated some respondents (56.7%) do not have back ground about (SA). The respondents in the Ministries of Agriculture assessed the Graduates in regard to agricultural skills, and confidence to perform duties as fair (10%), and good (23.3%), but, for reliability, managerial skills, tactic and ability to participate in forums as fair (6.7%). Good (27.7%), fair (3.3%), and good (30%) respectively. Assessment of the Graduates at Research Centers, were assessed in relation to Research methodology, statistical analysis, and writing scientific papers as good (40 %,).While for Software skills as excellent (100%), and for Agricultural Technology Transfer as very good (80%). While; the respondents from Faculties of Agriculture, assessed the Graduated for practical skills, teaching ability, skills of writing scientific papers, participation in workshops and seminars as good (93.3%), very good (6.7%), fair (6.7) and very good (33.3%), respectively. The Graduates’ quality is below the expectations. Based on the above findings, the study recommends the review of the whole educational system, Faculties of Agriculture to include the concepts of sustainable agriculture in their curriculum and give high consideration to practical part. In the same context, further study is recommended including the whole Country.
Keywords: Multistage; Respondents; institutions; curriculum